Peripheral and Central Fatigue Development during All-Out Repeated Cycling Sprints - Hureau, Thomas J; Ducrocq, Guillaume P; Blain, Gregory M (Medicine and science in sports and exercise, 2016)
We investigated the development and recovery of peripheral and central fatigue during repeated cycling sprints and its influence on power output. On six separate days, 12 healthy males performed the following tests: 1, 4, 6, 8, and 10 × 10 s sprints with 30 s of passive recovery between sprints, as well as 8 × 10 s sprints with 10 s of passive recovery. Peripheral and central fatigue levels were quantified via changes in preexercise- to postexercise-potentiated quadriceps twitch force, as evoked by supramaximal electrical stimulation of the femoral nerve (30 s through 6 min recovery), and quadriceps voluntary activation (VA), respectively. Root mean square of the vastus lateralis and the vastus medialis electromyogram during sprints were normalized by maximal M wave amplitude (RMS·Mmax). From the first to the sixth sprint, we found significant and gradual reductions in power output (-25% ± 7%), RMS·Mmax (-7% ± 4%), twitch force (-47% ± 11%) and VA (-11% ± 6%). During the subsequent sprints, no additional reduction in power output, RMS·Mmax, twitch force or VA, was found. Reduction in between-sprints recovery duration led to a significant reduction in power output and RMS·Mmax but no change in peripheral and central fatigue. These findings are consistent with the hypothesis that central motor command and power output during all-out repeated sprints are limited in order to prevent excessive locomotor muscle fatigue. They also demonstrate that both the peripheral and central fatigue contribute significantly to the decline in power output elicited via repeated sprints.